Portuguese emigration Factbook 2019 - Vidigal, Inês (2020)
In 2018, the Portuguese emigration decreased again, with about 80 thousand individuals leaving the country. Overall, the decline observed is strongly correlated with the recovery of the Portuguese economy, especially in terms of job creation (Pires, Pereira and Azevedo, 2018), as well as the reduction of the attraction of destination countries such as the United Kingdom, due to the Brexit, and Angola, due to the economic crisis triggered by the devaluation of oil prices. The 2019 edition of the Factbook includes data updated to 2018 (or last year available) on total Portuguese emigration and to the main destination countries, as well as on emigrants' remittances.